The Ethics of Authorship Communication, Seduction, and Death in Hegel and Kierkegaard - Berthold, Daniel (Fordham University Press, 2022)
This is a book about the ethics of authorship. Most directly, it explores different conceptualizations of the responsibilities of the author to the reader. But it also engages the question of what styles of authorship allow these responsibilities to be met. Style itself is an ethical issue, since the relation between the writing subject and the reader--and the dynamics of authority and influence, of gift giving and friendship in this relation--have as much to do with how one writes as what one says. The two writers who serve as the main subjects for this work, the German idealist philosopher G. W. F. Hegel and the Danish Christian existentialist Søren Kierkegaard, invite us to confront particularly challenging questions about the ethics of authorship.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 29. Mrz 2022)
Keywords: LITERARY CRITICISM / Books & Reading